2022
DOI: 10.1002/cctc.202101860
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of CMP‐Sialic Acid Synthetase and α2,3‐Sialyltransferase for Cascade Synthesis of 3′‐Sialyl β‐D‐Galactoside with Enzyme Reuse

Abstract: Sialo‐oligosaccharides are often synthesized via cascade reaction of CMP‐sialic acid synthetase (CSS) and sialyltransferase (SiaT). Here, we studied individual enzyme immobilization to develop solid‐supported preparations of the CSS from Neisseria meningitis (NmCSS) and the α2,3‐SiaT from Pasteurella dagmatis (PdSiaT). Oriented immobilization via N‐terminal His‐tag as well as “random” (orientationally uncontrolled) immobilization via multipoint covalent coupling gave catalyst preparations of each enzyme with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The oligosaccharide content change caused by adding sugar during processing has not yet been explained. From this study, it was speculated that monocrystal rock sugar (used in this study) could be hydrolyzed into glucose and fructose [ 28 , 29 , 30 , 31 ], in which the glucose could be dehydrated and condensed with galactose sialate by heat treatment to form 3′-sialyllactose. In sum, it showed that adding sugar (monocrystal rock sugar) could increase the nutritional value of edible bird’s nest products within the tested range.…”
Section: Resultsmentioning
confidence: 99%
“…The oligosaccharide content change caused by adding sugar during processing has not yet been explained. From this study, it was speculated that monocrystal rock sugar (used in this study) could be hydrolyzed into glucose and fructose [ 28 , 29 , 30 , 31 ], in which the glucose could be dehydrated and condensed with galactose sialate by heat treatment to form 3′-sialyllactose. In sum, it showed that adding sugar (monocrystal rock sugar) could increase the nutritional value of edible bird’s nest products within the tested range.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing a confinement and compartmentalization strategy enabled higher substrate concentrations to be used. Immobilization has also been used to improve the overall efficiency of sialyl galactoside synthesis using a two-step route from Neu5Ac . Initially, immobilization via N-terminus His-tags of CMP-sialic acid synthetase from Neisseria meningitis ( Nm CSS) and sialyltransferase from Pasteurella dagmatis ( Pd SiaT) yielded poor immobilizates in all instances (via affinity or epoxy on a range of commercial carriers).…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%
“…Immobilization has also been used to improve the overall efficiency of sialyl galactoside synthesis using a two-step route from Neu5Ac. 124 Initially, immobilization via N-terminus His-tags of CMP-sialic acid synthetase from Neisseria meningitis ( Nm CSS) and sialyltransferase from Pasteurella dagmatis ( Pd SiaT) yielded poor immobilizates in all instances (via affinity or epoxy on a range of commercial carriers). Therefore, constructs containing the Z basic2 protein module (a 7 kDa, 58 amino acid module with a high charge ratio) were made and tested, affording high immobilization yields and full activity recovery on all of the carriers versus the native enzymes ( Figure 6 ).…”
Section: Using Biocatalysis To Provide the Building Blocks For Bioche...mentioning
confidence: 99%
“…Due to multiple arginine residues clustered on one of its sides, the Z basic2 exhibits highly localized, positive charge density. , These properties enable strong protein binding on anionic supports for enzyme immobilization. A number of studies have shown that enzyme fusions with Z basic2 can be immobilized with excellent efficiency, partly due to the fact that the immobilization is orientationally controlled; that is, surface tethering occurs mainly via the Z basic2 module. ,, The current study was performed with the idea that mechanically and dimensionally stronger NFC/CMC-based scaffolds differing in pore sizes, interconnected morphology or structure, and negative surface charge might present a new class of solid supports for the immobilization of Z basic2 enzymes. The enzymes used in this proof-of-principle analysis were from the class of sugar-nucleotide dependent (Leloir) glycosyltransferases.…”
Section: Introductionmentioning
confidence: 99%